Education and Entrepreneurship Integration Strategy at State Islamic Institute of Bukittinggi - Harfandi Harfandi; Era Sonita; Zulhelmi Zulhelmi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2020)
The increasing number of graduates from State Islamic Institute of Bukittinggi (IAIN Bukittinggi), who do not have any competency from year to year, will increase the number of unemployed in the society. In this regard, this study aimed to formulate strategies in integrating education with entrepreneurship at State Islamic Institute of Bukittinggi in order to produce applicative and highly competitive graduates. After being analyzed using SWOT analysis, SWOT Matrix, and Weight Score Table, it can be concluded that the right strategies are; implementing the KKNI curriculum that suits market needs, developing curricula especially entrepreneurship courses, equipping students with adequate entrepreneurial knowledge, creating entrepreneurship training programs, such as holding student business units to develop students' entrepreneurial potential, and multiplying student entrepreneurship practices through collaboration with business actors.Dengan bertambahnya lulusan Institut Agama Islam Negeri (IAIN) Bukittinggi, yang tidak memiliki kompetensi dari tahun ketahun, akan menambah jumlah pengangguran di tengah-tengah masyarakat. Sehubungan dengan itu, penelitian ini bertujuan untuk merumuskan strategi dalam mengintegrasi pendidikan dan kewirausahaan pada Institut Agama Islam Negeri (IAIN) Bukittinggi guna menghasilkan lulusan yang aplikatif, dan berdaya saing tinggi. Setelah dianalisis dengan menggunakan analisa SWOT, Matrix SWOT, dan Tabel Bobot Skor, maka dapat dikemukakan bahwa strategi yang tepat adalah; mnerapkan kurikulum KKNI yang sesuai dengan kebutuhan pasar, mengembangkan kurikulum terutama mata kuliah kewirausahaan, membekali mahasiswa dengan pengetahuan kewirausahaan yang memadai, dan membuat program-program pelatihan kewirausahaan, seperti mengadakan unit-unit usaha mahasiswa untuk pengembangan potensi wirausaha mahasiswa, serta memperbanyak praktek-praktek kewirausahaan mahasiswa, melalui kerjasama dengan para pelaku usaha.